Evaluation of the Immune Response in Scabies Patient (Ordinary and Prisoners) Treated with Permethrin 5% (Medico Legal Update, 2020)
Scabies is a common parasitic infection, caused by sarco-sarcoptes, the infection occurs when the Sarcoptes penetrates the corneal layer of the skin, predominant pathological manifestations, through inflammatory andallergic reactions to mite products.This study is designed to obtain the Evaluation of the immune responsein scabies patient (Ordinary and Prisoners) treated with Permethrin 5%.The study included (28)OrdinaryScabies patients, (32) prisonersas well as a (30)healthy person as a control group. Blood samples werecollected from all studied groups Enzyme-linked immunosorbent assay (ELISA) was used to measureInterleukine-4,IL-9 and total IgE.Results of the study showed that serum,IL-4 showed a significant (P?0.0001) increasing in prisoners compared to ordinary patients and control groups(248.8±19.3vs.79.2±10.7pg/ml),(248.8±19.3vs.73.9±5.5pg/ml)respectively,while IL-9 showed a significant (P? 0.001), increasing incontrol compared to Ordinary Scabies patients group and prisoners (506.9±48.7vs.337.8±18.2 pg/ml),(506.9±48.7 vs. 424.1±36.5 pg/ml) respectively in post- treatment, There was positive correlation between(IL-4 and IgE).Levels of two cytokines (IL-4, and IL-9) were assessed in sera of Ordinary ScabiesPatientsand control group, IL-4 showed a significant (P?0. 0001) increasing in Ordinary Scabies comparedto controlgroup (92.5±7.0 vs. 73.9 ± 5.5pg/ml), respectively. While IL-9with asignificant decreasinglevel inOrdinaryScabies patients compared to control group(97.8 ±18.8 vs. 506.9 ±48.7 pg/ml) in pre-treatment, level ofIgE were recorded in pre- treatment in ordinary patients and prisoners (314.8±37.5 vs. 17.8±3.7 IU/ml),(372.7±37.5 vs. 17.8±3.7 IU/ml) respectively, were a significantly increasing (P=>0.05) as compared tohealthy control. In post- treatment IgE levels show a significantly lowering (P=>0.05), in prisoners thanOrdinary patients(14.5±1.7 vs. 33.3±2.4 IU/ml).